Dampak Stagnasi Pendidikan Menengah-Tinggi terhadap Pembangunan Ekonomi dan Modal Manusia di Sulawesi Tenggara: Implikasi bagi Kebijakan Keuangan Daerah - Murniati Murniati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This research aims to analyze the impact of stagnation in secondary-higher education on economic development and human capital in Southeast Sulawesi and to examine its implications for regional financial policies. Using a systematic literature review approach based on BPS data, empirical journals, and the latest education policies, this research finds that stagnation in access and quality of secondary-higher education is reflected in low school participation rates, decreasing average years of schooling, and significant regional and social group disparities. Structural barriers such as poverty, limited educational infrastructure, disparities in teacher distribution, and the effectiveness of educational aid policies are the main causes. Consequently, the workforce structure is dominated by lower secondary graduates, educated unemployment and informal workers remain high, and the demographic bonus has not been optimally utilized for regional economic transformation. The findings of this research indicate that regional fiscal policies—particularly the allocation of education budgets and the effectiveness of assistance programs—still need to be significantly improved, especially for secondary-higher education and underdeveloped areas. The reformulation of budget management strategies, improvement of education aid governance, and cross-sector collaboration are the main recommendations to ensure that education investments truly impact the enhancement of human capital quality and inclusive economic growth. This research also highlights the importance of data-driven policy innovation and strengthening the monitoring of educational programs to accelerate the sustainable transformation of human development in Southeast Sulawesi.